A SOCIO-PERCEPTUAL/ECOLOGICAL APPROACH TO LEXICAL DEVELOPMENT: AFFORDANCES OF THE COMMUNICATIVE CONTEXT - Goldring, Patricia Goldring (Anales de Psicología / Annals of Psychology)
Basic assumptions crucial to the innatist position influence researchers to ignore the source of language input, its characteristics, and its impact on language development. However, a key assumption of the socio-perceptual/ecological approach is the idea that the emergence of language depends on the dynamic structure of the social-interactive environment in which the infant develops. To support and illustrate this perspective, evidence from a series of studies examining the social and perceptual bases of the emergence of the lexicon is marshalled to support and illustrate this perspective. Parallel arguments can and ought to be constructed to explain other aspects of language learning.